An alternative framework of open source Enterprise Resource Planning (ERP) system for Small and Medium Enterprise (SME) - Baharum, Zirawani; Ngadiman, Salihin; Haron, Habibollah (2008)
Integrated enterprise systems deserve intensive research because of their great potential for financial, technical, managerial, human, strategic benefits, costs, and risks.As ERP is an important tool that offers full package of managing and integration of data’s, Open source was a package in the business world for optimization which offers organization with lowest cost and perfect reliability suite to SMEs. However, facing challenges of SMEs today the right solution should have every goods and best from both of these tools.Therefore, Open Source ERP is the new evolution that derives from both tools promising more extensive functionality in business demands.